Enhancing the Crack Resistance of Polyester Resin Composites with Rice Husk Fiber Reinforcement - Nusyirwan, Nusyirwan; Hijar, Yul; Malik, Adam (Talenta Publisher, 2025)
Polymers have been widely developed as alternative materials to replace metal materials due to various advantages such as low density and an easy manufacturing process. Still, polymers have many disadvantages, including not having high mechanical strength, easy to crack when hit by impact. One of the materials studied is an unsaturated polyester polymer widely used for composite matrices in vehicle structural components, aircraft and ship bodies, and vehicle components. One of the studied fibers is rice husk particle fiber. The study of cracks is crucial because it causes the material to no longer be able to support the load according to the previous plan and causes failure to occur more quickly. One way to overcome material failure due to cracks in the composite material is to prevent crack propagation by adding reinforcing material. In this study, a composite material was made using rice husk fiber to increase the crack resistance of the polyester composite matrix. From the results of crack testing, there is a tendency to increase the percentage of rice husks by 5%, 10%, 15%, and 20%. The value expected to be obtained for determining the crack resistance of the material is the value of the stress intensity factor (K1). The largest K1 value was obtained at the variable percentage of rice husk 15% with MMA as much as 10% and MEKP 4% obtained a stress intensity factor of 1,558 MPa.m0.5; this value can increase the value of the stress intensity factor of pure polyester K1 by 0.667 MPa.m0.5 which shows an increase of 233.58%.